2013
DOI: 10.1002/ajmg.a.36206
|View full text |Cite
|
Sign up to set email alerts
|

Variable approaches to genetic counseling for microarray regions of homozygosity associated with parental relatedness

Abstract: SNP microarrays are capable of detecting regions of homozygosity (ROH) which can suggest parental relatedness. This study was designed to describe pre- and post-test counseling practices of genetics professionals regarding ROH, explore perceived comfort and ethical concerns in the follow-up of such results, demonstrate awareness of laws surrounding duty to report consanguinity and incest, and allow respondents to share their personal experiences with results suggesting a parental relationship. A 35 question su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It is increasingly becoming a challenge about how to respond to and counsel for such results, and a need for genetics professionals to have a guideline has been requested. 18 The ethical, legal and social outcomes that these cases present and the approaches to dealing with the same are still evolving. 18,19 In the sibling studies, the result showed only 13 of 23 families (B57%) had a concordant result in prediction of parental relatedness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is increasingly becoming a challenge about how to respond to and counsel for such results, and a need for genetics professionals to have a guideline has been requested. 18 The ethical, legal and social outcomes that these cases present and the approaches to dealing with the same are still evolving. 18,19 In the sibling studies, the result showed only 13 of 23 families (B57%) had a concordant result in prediction of parental relatedness.…”
Section: Discussionmentioning
confidence: 99%
“…18 The ethical, legal and social outcomes that these cases present and the approaches to dealing with the same are still evolving. 18,19 In the sibling studies, the result showed only 13 of 23 families (B57%) had a concordant result in prediction of parental relatedness. Although in some families such as family 3 (Table 1b), three siblings had almost exact amount of ROHs (B876 Mb), for other families, ROH from one sibling alone will not reliably predict the degree of relatedness between parents.…”
Section: Discussionmentioning
confidence: 99%
“…As SNP microarray is still a relatively new technology, clinician interpretation of these results and patient care related to results of homozygosity are quite variable. Clinician follow-up for results of homozygosity was the focus of the survey by Grote et al [15] . The study assessed clinician comfort level in receiving/ reporting results of homozygosity, pre-and post-test counseling for microarray results of homozygosity, patient reactions to results of homozygosity, and physician understanding of laws related to the duty to report incest.…”
Section: Disclosing Results Of Homozygosity To Patientsmentioning
confidence: 99%
“…The American College of Medical Genetics and Genomics (ACMG) issued a guidance document in 2013 which focused on detection and downstream communications with ordering clinicians [12] . These guidelines as well as other publications have addressed the essential role of pre-test counseling for patients and their families ensuring that families understand that SNP microarray testing can reveal consanguinity [15,16] . The ACMG guidelines also recommend that each laboratory should establish a size threshold for inclusion of ROH in genomic calculations, suggesting 2-5 Mb as a potential threshold, excluding the X chromosome.…”
Section: Guidelines For Reporting Suspected Consanguinitymentioning
confidence: 99%
See 1 more Smart Citation